Vitamin D deficiency among Moroccan women aged 18 to 65 years in the region of Rabat-Salé-Kénitra, Morocco - leftat, Loubna; Belghiti, Hakim; Chouari, Rihab; Ibrahmi, Btihaj AL; Khal-Layoun, Soad; Bour, Abdellatif (Edelweiss Applied Science and Technology, 2025)
Vitamin D deficiency is a significant public health issue, affecting nearly one billion people worldwide and influencing both bone and overall health. This cross-sectional study aimed to assess the prevalence of vitamin D inadequacy among Moroccan women and explore its relationship with body mass index and parathyroid hormone levels. Conducted at the Military Hospital of Rabat from June 2014 to June 2015, it included 718 women aged 18 to 65 who presented with overweight or obesity. Anthropometric measurements and blood samples were collected to assess levels of 25-hydroxyvitamin D, parathyroid hormone, and calcium. The findings revealed that 41.08% of participants were classified as moderately deficient in vitamin D, while 24.37% were severely deficient. The median serum 25(OH)D level was significantly lower in deficient women (11 µg/L) compared to those with normal levels (26 µg/L). Furthermore, parathyroid hormone levels increase while vitamin D levels decrease, revealing a significant inverse correlation (R² = 0.002) and the linear regression between body mass index and vitamin D concentration indicating an inverse relationship between the two parameters (R² = 0.004). These results underscore the need for sustainable vitamin D supplementation to improve the health of Moroccan women and mitigate associated risks.